Formulation and optimization of silymarin-encapsulated binary micelles for enhanced amyloid disaggregation activity. (2nd November 2021) - Singh, Ajit; Ujjwal, Rewati Raman; Kumar, Ashish; Verma, Rahul K.; Shukla, Rahul
Abstract: Silymarin (SLY) is a natural hydrophobic polyphenol that possesses antioxidant and amyloid fibril (Aβ1–42 ) inhibition activity, but its activity is hindered due to low aqueous solubility. In this study, SLY is encapsulated in binary micelle (SLY-BM) that has been utilized to enhance the Aβ1–42 fibril disaggregation. To enhance the aqueous solubility, SLY payload in micelles were optimized using Box–Behnken Design (BBD) to increase the efficiency of Aβ1–42 fibril disaggregation. BBD was used to investigate the effect of ratio of Solutol HS15:Poloxamer-188, amount of acetone and hydration volume on critical quality attributes, particle size, and entrapment efficiency for SLY-BM. Furthermore, SLY-BM was characterized for its physical and drug release properties. The Aβ1–42 fibril disaggregation and antioxidant studies were monitored using spectroscopic and microscopic techniques. BBD optimized the particle size <50 nm with %EE > 80%, and solubility factor of SLY-BM was enhanced to 460 folds than free SLY. Inhibitory concentration 50% (IC50 ) value of SLY-BM was 19.67 µg/mL compared to free SLY (30.06 µg/mL) in diphenylpicrahydrazyl assay. SLY-BM increased the Aβ1–42 disaggregation compared to free SLY observed via thioflavin-T assay, photon correlation spectroscopy, and circular dichorism. Further morphological evaluation of Aβ1–42 disaggregation was monitored by microscopy which showed that SLY-BM disaggregated the fibrils in 48 h. According to our findings, we concluded that SLY-BM micelles are potential candidates for delivery of neuroprotective agents.